Coconut milk yogurt production plant - Besillas, Romeo L. Jr; Co, Rommel P.; Lagasca, Vicente L. Jr; Vergel De Dios, Alexander B. (College of Engineering, 1998)
Project title: Coconut Milk Yogurt Production Plant -- Plant location: Tanza, Cavite -- Total land area: 2200 sq.m. -- Total plant capacity: 3,592,800 kg/yr. -- Total capital investment: 96,814,920 Php/yr -- Total product cost: 160,772,955 Php/yr. -- Selling price: 125g - Php 15, 200g - Php 24 -- Return on investment: 74.65% -- Payback period: 11 months